Bhinneka Tunggal Ika: Indonesia Circumscribed Norm Multiculturalism - Hartanti, Priskila Shendy; Ardhana, Dwi (Global: Jurnal Politik Internasional, 2022)
Norm of Multiculturalism deals with the acceptance and accommodation of differences in society. In the West, it is an approach that guarantees equal rights among white settlers, indigenous people, and the immigrants. It provides the idea that everyone can live together in harmony despite differences in their cultural background. Asian countries have different narratives of multiculturalism as – most of them - were built upon heterogeneity, hence they were accustomed to living in diversity. By utilising qualitative research method, this paper presents a new conception of ‘circumscribed multiculturalism’ based on the practice of Bhinneka Tunggal Ika in Indonesia. Bhinneka Tunggal Ika is the country’s official slogan that describes the openness of the country to cultural differences, but with certain conditions that limit the openness. This article concludes that the circumscribed multiculturalism not only preserves Indonesia's national identity from the intervention of western and other external values but also withholds some traditional/local practices that might not be accepted by wider society.